GAMBARAN RESPON FISIK DAN PSIKOLOGIS DISMENORE PADA REMAJA PUTRI USIA 13 -15 TAHUN DI SMPN 5 KOTA KUPANG - Julio Da Costa (STIKes CHMK, 2018)
Dysmenorrhea is pain arising prior to, when or during menstruation. Arising dysmenorrhea in adolescents in general are not caused by pathology, but due to hormonal imbalance. Pain during dysmenorrhea can cause physical and psychological response. Physical response can complain when dysmenorrhea is pain in the lower abdomen, low back pain can be accompanied by anorexia, nausea, vomiting and some have experienced loss of consciousness or fainting. In addition there is a psychological response, such as mood disorders, restless, unable to concentrate, and a decline in interest in routine activities. The purpose of this study to determine how the physical and psychological response of dysmenorrhea in adolescents. The research method used is descriptive analytic study with cross sectional approach, population in this study that adolescents who experience menstruation and aged 13 to 15 years by 110 students. Sampling technique used is porposivi sampling with the number of respondents 86 students. Measuring instruments used in this study using kuesioner. The results showed physical response with the highest pravalensi by 70% (60 respondents) respondents had complaints of pain in the lower abdomen. While the psychological response to the highest pravalensi 77% (66 respondents) had complaints of long lazy. This study is expected to be further research and educational institutions should be able to work with relevant agencies or health professionals to provide information to adolescents about dysmenorrhoea. Information on dysmenorrhea in adolescents should be given early, so teens do not think of dysmenorrhea is an abnormality or a pathology Keywords: Dysmenorrhea Physical and Psychological response